Micros y Pequeñas Empresas Latinas Frente al Poderoso Desafío de la Administración Estratégica (2013)
MSMEs in Latin America have a major role but lack significant support for training of entrepreneurs and professionals that lead them to compete with advantages in the national and global environment. An internal element that makes the difference between companies is the use of strategic management for their senior. Failure to achieve the latter, lies mainly in higher education institutions, which have not generated the instances necessary for increasing the university - enterprise.